2016
DOI: 10.18410/jebmh/2016/1093
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Morbidity Profile Among Elderly Persons in a Rural Area of Kozhikode District

Abstract: BACKGROUND World population is aging, which is a concern of 21 st century because of advances in medical sciences and improved social conditions. In developing countries like India where aging occurs rapidly due to the phase of demographic transition characterised by rapid fertility decline and increase in life expectancy. In India for the year 2010, the estimates are 8% of total population are above the age of 60 years and is likely to rise to 19% by 2050. Aging is a time of multiple illness and general disab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
3
1
0
Order By: Relevance
“…9 Banjare et al and many other researchers reported that majority of these people were married. 10,12,15 Similar findings were reported in our study in which 72.5% geriatric people were married followed by 27.5% widow/widowers. In our study, majority of the study subjects (51.7%) were living independent, followed by people who were totally dependent on others (48.3%).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…9 Banjare et al and many other researchers reported that majority of these people were married. 10,12,15 Similar findings were reported in our study in which 72.5% geriatric people were married followed by 27.5% widow/widowers. In our study, majority of the study subjects (51.7%) were living independent, followed by people who were totally dependent on others (48.3%).…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were observed in studies conducted by different researchers like Bharati et al and many others. [8][9][10][11][12] Like studies conducted by Chaudhary et al and many others, the number of male subjects was predominant in our study as compared to number of females. 10,13,14 But in some other studies conducted by Sahu et al and other researchers, proportion of female subjects outnumbered male study subjects.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations